Factors associated with neck pain in fighter aircrew: a systematic review and meta-analysis. (31st March 2021) - Wallace, James B; Newman, Phil M; McGarvey, Aoife; Osmotherly, Peter G; Spratford, Wayne; Gabbett, Tim J
Abstract : Neck pain is a common complaint among fighter aircrew, impacting workforce health and operational capability. This systematic review aimed to identify, evaluate and synthesise the current evidence for factors associated with the occurrence of neck pain among fighter aircrew. Six electronic databases were searched in June 2019 and updated in June 2020 utilising the maximum date ranges. Included studies were appraised for methodological quality, ranked according to level of evidence and relevant data extracted. Where methods were homogeneous and data availability allowed, meta-analyses were performed. A total of 20 studies (16 cross sectional, one case–control, one retrospective cohort and two prospective cohort) were eligible for inclusion. Of the 44 factors investigated, consistent evidence was reported for greater occurrence of neck pain among aircrew operating more advanced aircraft and those exposed to more desk/computer work, while another 12 factors reported consistent evidence for no association. Of the 20 factors where meta-analyses could be performed, greater occurrence of neck pain was indicated for aircrew: flying more advanced aircraft, undertaking warm-up stretching and not placing their head against the seat under greater +Gz. Despite many studies investigating factors associated with neck pain among fighter aircrew, methodological limitations limited the ability to identify those factors that are most important to future preventive programmes. High-quality prospective studies with consistent use of definitions are required before we can implement efficient and effective programmes to reduce the prevalence and impact of neck pain in fighter aircrew. PROSPERO registration number: CRD42019128952. Neck pain is a common complaint among fighter aircrew, impacting workforce health and operational capability. This systematic review aimed to identify, evaluate and synthesise the current evidence for factors associated with the occurrence of neck pain among fighter aircrew.